Association of MPV, NLR, PLR and CRP on testicular salvage in testicular torsion: A systematic review and meta-analysis - Brodjonegoro, Sakti R.; Rizal, Dicky M.; Arfian, Nur; Luzman, Raedi A.; Pikatan, Narpati W.; Robert, Robert; Febriyanto, Toni; Liliana, Belinda; Yogahutama, Noka; Dwiaji, Iqbal W. (Narra J, 2025)
Testicular torsion, a critical urological emergency caused by twisting of the spermatic cord, poses a risk of ischemia, particularly in children who often struggle to pinpoint symptoms onset. Delay in managing testicular torsion can lead to the need for orchiectomy. The aim of this study was to assess the association between hematologic parameters—mean platelet volume (MPV), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and C-reactive protein (CRP)—and testicular salvage in cases of testicular torsion. Four databases (PubMed, Embase (Ovid), Science Direct, and Scopus) were systematically searched for eligible studies published up to November 4, 2024. The primary outcome was testicular salvage. Sensitivity analysis was performed using leave-one-out plot. Subgroup analysis was performed based on age, country, region, duration to orchiopexy and duration to orchiectomy. Heterogeneity was examined using I² statistics, and a random-effect model was applied. Out of 363 studies identified, nine observational studies involving 796 patients were included, with 338 (42.3%) in orchiopexy group. The meta-analysis indicated that MPV value was significantly elevated in orchiectomy group (mean difference (MD): -0.4; 95% confidence interval (95%CI): -0.62–(-0.18); p<0.01), with higher MPV levels associated with an increased likelihood of orchiectomy (odds ratio (OR): 2.12; 95%CI: 1.35–3.33; p<0.01). NLR, PLR, and CRP showed no significant association with testicular salvage, as demonstrated by pooled MD and OR analyses (p>0.05). No significant differences were observed after sensitivity and subgroup analysis (p>0.05). These findings suggest that elevated MPV levels are associated with non-salvageable testis, requiring orchiectomy highlighting its potential utility in clinical evaluation for testicular torsion.